POST-COVID-19 AUTOIMMUNE DISEASES: CHALLENGES AND PERSPECTIVES IN TRANSLATIONAL IMMUNOLOGY - Clares , Daiana Martins; Machado, Mitzy Stephanny; Leite, Ana Júlia da Silva Rodrigues Carvalho; da Silva, André Valério; Oda, Juliano Yasuo; Machado, Aline Rafaela da Silva Rodrigues; Machado, Alex Martins (Editora Impacto Científico, 2025)
The COVID-19 pandemic has highlighted not only the direct impacts of SARS-CoV-2 infection but also its potential role as a trigger for autoimmune diseases. Several immunopathological mechanisms have been identified, including cytokine storm, regulatory T cell dysfunction, exacerbated B cell activation, molecular mimicry, and NET formation, all capable of breaking immune tolerance. Increasing evidence shows the presence of multiple autoantibodies in post-COVID patients, such as ANA, anti-DNA, anti-TPO, anti-GAD, and ANCA, suggesting an increased risk of autoimmune conditions. Among the diseases described after infection are: Guillain-Barré syndrome, systemic lupus erythematosus, rheumatoid arthritis, seronegative arthritis, type 1 diabetes, Hashimoto's disease, multiple sclerosis, inflammatory myopathies, and vasculitis. Documented clinical cases reinforce this association, illustrating both acute and chronic presentations in individuals with no prior history of autoimmunity. Although the mechanisms are not yet fully understood, a convergence between genetic predisposition, persistent inflammation, and viral triggers is observed. The role of COVID-19 vaccines is also debated: although essential in containing the pandemic, reports of rare autoimmune events suggest that, in susceptible individuals, they may act as an additional trigger. However, the benefits far outweigh the risks. Clinical implications include the need for prolonged surveillance of post-COVID patients, early autoantibody screening, and personalized therapeutic strategies. Future prospects involve the development of predictive biomarkers, targeted immunomodulatory therapies, and multicenter registries to better understand the relationship between COVID-19 and autoimmunity. Thus, COVID-19 establishes itself as a unique model for studying how viral infections can precipitate autoimmune diseases on a population scale.DOI: https://doi.org/10.56238/edimpacto2025.066-001